Efficient Synchronization of CRDTs Using VCube-PS - Galesky, Leonardo Freitas; Rodrigues, Luiz Antonio; Duarte Jr., Elias Procópio; Arantes, Luciana (Anais do Latin-American Symposium on Dependable Computing (LADC); 2023: Anais do XII Latin-American Symposium on Dependable Computing, 2023)
This work presents VCube-Sync, a distributed datastore that uses the VCube virtual topology to maintain Conflict-free Replicated Data Types (CRDT). CRDT can ensure consistency in a deterministic and conflict-free manner. The VCube has been previously used to implement multiple distributed systems abstractions, due to its properties, in particular fault tolerance and logarithmic latency. The VCube-Sync protocol presented in the present work is based on VCube-PS, a publish-subscribe system based on VCube. VCube-Sync exploits the synergy between VCube-PS and replication systems. Evaluation experiments with VCube-Sync in the context of operations-based CRDTs were performed on the Grid5000 testbed under various loads and network distributions. The experiments include comparisons with EcoSyncTree, another replication protocol recently proposed. The results show that VCube-Sync offers superior performance in terms of latency, scalability, and bandwidth.